Answer:
![y=(1)/(3)x](https://img.qammunity.org/2021/formulas/mathematics/college/v1fljo40ij80q46tvdgu680n6t3nxorewf.png)
Explanation:
The given line segment has a midpoint at (3, 1) and goes through (2, 4), (3, 1), and (4, -2). We can use any two of the three points to calculate the equation of the line. Let us use the points (2, 4) and (4, -2)
Therefore the line goes through (2, 4) and (4, -2). The equation of a line passing through
is:
.
Therefore the line passing through (2, 4) and (4, -2) has an equation:
![(y-y_1)/(x-x_1)=(y_2-y_1)/(x_2-x_1)\\(y-4)/(x-2)=(-2-4)/(4-2)\\(y-4)/(x-2)=(-6)/(2)\\y-4=x-2(-3)\\y-4=-3x+6\\y=-3x+10](https://img.qammunity.org/2021/formulas/mathematics/high-school/ky3zcj56anamimk4z7w2w0k19vfjfxy0qy.png)
Comparing with the general equation of line: y = mx + c, the slope (m) = -3 and the intercept on the y axis (c) = 10
Two lines are said to be perpendicular if the product of their slope is -1. If the slope of line one is m1 and the slope of line 2 = m2, then the two lines are perpendicular if:
.
Therefore The slope (m2) of the perpendicular bisector of y = -3x + 10 is:
![m_1m_2=-1\\-3m_2=-1\\m_2=(1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4f2xuhk35fz808z85xob701yw8l47p5vin.png)
Since it is the perpendicular bisector of the given line segment, it passes through the midpoint (3, 1). The equation of the perpendicular bisector is:
![(y-y_1)/(x-x_1)=m\\(y-1)/(x-3)=(1)/(3)\\ y-1= (1)/(3)(x-3)\\ y-1=(1)/(3)x-1\\y=(1)/(3)x](https://img.qammunity.org/2021/formulas/mathematics/high-school/l0sh9z14lbf1bjp1jfhizzvi6w813351tu.png)
the equation, in slope-intercept form, of the perpendicular bisector of the given line segment is
![y=(1)/(3)x](https://img.qammunity.org/2021/formulas/mathematics/college/v1fljo40ij80q46tvdgu680n6t3nxorewf.png)